2009
DOI: 10.3748/wjg.15.3261
|View full text |Cite
|
Sign up to set email alerts
|

Specific probiotics alleviate allergic rhinitis during the birch pollen season

Abstract: AIM:To investigate whether birch pollen allergy symptoms are linked with gut microbiota changes and whether probiotics have an effect on these. METHODS:Forty seven children with confirmed birch pollen allergy were randomized to receive either a probiotic combination of Lactobacillus acidophilus (L . a c i d o p h i l u s ) N C F M T M ( ATC C 7 0 0 3 9 6 ) a n dBifidobacterium lactis (B. lactis ) Bl-04 (ATCC SD5219) or placebo in a double-blind manner for 4 mo, starting prior to onset of the birch pollen seaso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
81
0
5

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(91 citation statements)
references
References 28 publications
(34 reference statements)
2
81
0
5
Order By: Relevance
“…The strains were included either as single freeze-dried cultures at a dose of 2.5 × 10 9 colony-forming units (cfu), or in a combination of two strains ( L. acidophilus NCFM + B. lactis Bl-04, 5 × 10 9 cfu [6]) or as all four strains combined (HOWARU Restore, 10 10 cfu [7]). The dose of the strains used in the simulations was similar to the daily doses used in two human intervention studies, of 5 × 10 9 and 1.7 × 10 10 cfu, respectively [6,7]. Counts of the single strains were controlled by flow cytometry of the bulk material [8], and the multi-strain products were composed accordingly.…”
Section: Methodsmentioning
confidence: 99%
“…The strains were included either as single freeze-dried cultures at a dose of 2.5 × 10 9 colony-forming units (cfu), or in a combination of two strains ( L. acidophilus NCFM + B. lactis Bl-04, 5 × 10 9 cfu [6]) or as all four strains combined (HOWARU Restore, 10 10 cfu [7]). The dose of the strains used in the simulations was similar to the daily doses used in two human intervention studies, of 5 × 10 9 and 1.7 × 10 10 cfu, respectively [6,7]. Counts of the single strains were controlled by flow cytometry of the bulk material [8], and the multi-strain products were composed accordingly.…”
Section: Methodsmentioning
confidence: 99%
“…A few published studies in the field of probiotics and AR are in line with our observations in this clinical trial and have showed a beneficial effect of the probiotic strains only after a 44-week administration. 16,19,21,30,31 We implemented the whole-blood assay and the basophil activation test in the current setting to correlate immune parameters to allergic symptoms and to be in alignment with recent recommendations suggested for probiotic-focused clinical trials. 32,33 It is well known that in allergic individuals, significant cytokine levels are induced upon ex vivo stimulation 28,34 and such increases in cytokine levels can be modulated by administration of mainstream treatments such as corticosteroids.…”
Section: Discussionmentioning
confidence: 99%
“…From the available evidence, it seems that probiotics have no impact on microbiota. In the treatment of rhinitis with L. acidophilus NCFMTM, fecal probiotic cell counts correlated positively with fecal acetic, propionic and butyric acid concentrations (Ouwehand et al, 2009), suggesting that the presence of L. acidophilus NCFMTM increases microbial fermentation in the colon. However, the colonization pattern did not differ between groups that consumed the probiotic strains and placebo.…”
Section: Effects Of Probiotics On Microbiota Compositionmentioning
confidence: 93%
“…Treatment with LGG resulted in a trend towards elevated fecal IgA levels, and this effect was significant in IgE-associated cow-milk allergy infants, suggesting maturation of intestinal immunity and triggering of a mechanism to protect the gut from the offending food (Viljanen et al, 2005a). In older subjects with a mature immune system and suffering from allergic rhinitis, fecal IgA concentrations increased in the placebo group during the pollen season; this increase was prevented by L. acidophilus NCFMTM (Ouwehand et al, 2009). Probiotics have also been reported to decrease the levels of fecal inflammatory markers, but this is controversial: findings differ between studies and strains used.…”
Section: Gut Immunity and Barrier Effectmentioning
confidence: 95%
See 1 more Smart Citation